CHARACTERISTICS OF ARTICLE AND CHARACTERISTICS OF CITATION IN THE JURNAL BAHASA DAN SENI - Malta Nelisa (Fakultas Bahasa dan Seni UNP, 2014)
KARAKTERISTIK ARTIKEL DAN KARAKTERISTIK SITIRAN DALAM JURNAL BAHASA DAN SENIAbstractThis study aims to identify and describe the characteristics of article and the characteristics of citation in the “Jurnal Bahasa dan Seni” in the following aspects. (1) Characteristics of articles related to the article distribution, article authorship patterns, and study subjects in the article. (2) Characteristics of citations related to the number of citations of documents, document forms, the citation, citation age, and patterns of authorship of the cited documents.Keywords: bibliometric, citation, authorshipAbstractPenelitian ini bertujuan untuk mengidentifikasi dan menggambarkan karakteristik artikel dan karakteristik sitiran dalam “Jurnal Bahasa dan Seni” dalam aspek berikut. (1) Karakteristik artikel yang berhubungan dengan distribusi artikel, pola artikel penulis, dan subyek penelitian dalam artikel. (2) Karakteristik kutipan yang berkaitan dengan jumlah kutipan dari dokumen, bentuk dokumen, kutipan, usia kutipan, dan pola kepengarangan dokumen yang dikutip. Kata Kunci: bibliometrik, sitiran, kepengarangan